(untitled) (Bangladesh Critical Care Journal, 2015)
Intensive care unit (ICU) based rehabilitation has become an important evidence-based component in the management of patients with critical illness. In addition to critical illness, prolonged bed rest and immobility may lead to severe physical deconditioning and loss of muscle mass and muscle weakness. Intensive care unit acquired weakness is associated with increased duration of mechanical ventilation and weaning, longer ICU and hospital stay, and increased mortality. These physical impairments may last for years after ICU discharge. Early Physical Medicine and Rehabilitation (PM&R) interventions in the ICU may attenuate or prevent the weakness and physical impairments occurring during critical illness. This article reviews the effects of prolong bed rest and inactivity, early PM&R interventions, their safety, feasibility, benefits and future directions for early PM&R in the ICU. Bangladesh Crit Care J September 2015; 3 (2): 63-66